1994
DOI: 10.1001/jama.1994.03520080053043
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibody to Inner Ear Proteins in Patients With Progressive Hearing Loss

Abstract: These results indicate that the presence of circulating antibody to a 68-kd constituent of bovine inner ear extract serves as a marker for IPBSNHL and that its presence correlates with disease activity and responsiveness to corticosteroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(48 citation statements)
references
References 12 publications
0
47
1
Order By: Relevance
“…Recently, Billings et al [24] reported that the 68-kD band may represent the highly inducible heat shock protein 70 by specific binding to monoclonal antibodies and migration in two-dimensional SDS gel electrophoresis. The report was confirmed subsequently through the protein sequence of this protein by Moscicki et al [22]. The importance of the antibody against this nonspecific stress protein in patients with inner-ear disease, especially PSNHL and Meniere's disease, is not clear at present, and further investigations arc required.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, Billings et al [24] reported that the 68-kD band may represent the highly inducible heat shock protein 70 by specific binding to monoclonal antibodies and migration in two-dimensional SDS gel electrophoresis. The report was confirmed subsequently through the protein sequence of this protein by Moscicki et al [22]. The importance of the antibody against this nonspecific stress protein in patients with inner-ear disease, especially PSNHL and Meniere's disease, is not clear at present, and further investigations arc required.…”
Section: Discussionmentioning
confidence: 81%
“…Overall, 32% of their patients with PSNHL demonstrated a positive reaction at 68 kD on Western blot assay using bovine inner ear [24], Subsequently, two different groups confirmed their re sults under similar experimental conditions [22,25], Moreover, Moscicki et al [22] demonstrated a significant relationship between positive blots against a 68-kD pro tein and disease activity or efficacy of steroid therapy on hearing loss. In this study, we found positive blots against a 67-kD protein in 4 of 25 (16.0%) patients with Me niere's disease, 1 of 2 (50.0%) patients with PSNHL, and 1 of 18 (5.6%) patients with other inner-ear diseases, com pared with 0% of controls.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An imaging study (MRI) was performed to rule out abnormalities of the eighth cranial nerve. The following criteria were applied to support a high suspicion of IMIED [15][16][17] : (1) A positive response was defined as (1) an improvement in pure tone average at 250, 500, 1,000, 2,000 and 4,000 Hz of more than 10 dB and/or (2) the elimination or marked alleviation of vertiginous symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Progressive SNHL The diagnosis of progressive SNHL was based on criteria reported by Moscicki et al [8] . Thirty-nine patients (16 men and 23 women; mean age 42.2 years; age range 15-69 years) were included.…”
Section: Sudden Snhlmentioning
confidence: 99%